Analysis of regional photovoltaic power generation suitability in China using multi-source data - Tong, Hongju; Lv, Ziyu; Jiang, Junyi; Gao, Xingguo; Wang, Ziqing; You, Chaoshuai; Xu, Kun; Wu, Yuhang; Pan, Xin (Frontiers in Earth Science, 2025)
IntroductionSolar photovoltaic (PV) power generation, a crucial part of global renewable energy, has been advancing swiftly. However, effective promotion of PV generation relies not only on enhancing generation efficiency but also on thorough evaluations of construction suitability. This study addresses this gap by developing a comprehensive evaluation framework for assessing the suitability of photovoltaic power station locations in China.MethodsThis research developed a subjective-objective evaluation framework that integrates the Analytic Hierarchy Process (AHP) and the Criteria Importance Through Intercriteria Correlation (CRITIC) method. This framework allows for a comprehensive analysis of photovoltaic power station location suitability. Long-term meteorological data and remote sensing products were used to calculate solar radiation and photovoltaic potential data, which were then applied to evaluate the suitability of photovoltaic generation across China.ResultsThe study revealed that from 2000 to 2020, China's average annual solar radiation was 5,896.437 MJ·m−2, and the total photovoltaic generation amounted to 1.10726 × 1015 KWh. By 2020, the average score for photovoltaic construction suitability in China was 0.1058, with suitable areas comprising 51.1% of the national territory. High-suitability regions were primarily concentrated in Northwest China, including Xinjiang and Gansu, where suitability scores exceeded 7.5 and annual generation surpassed 213 KWh. In contrast, southeastern coastal and southern provinces such as Jiangsu, Zhejiang, and Fujian exhibited lower suitability scores (<3.5) and annual average generation of less than 19.2262 KWh, primarily due to limited land availability and reduced solar radiation.DiscussionThe findings emphasize the critical need to prioritize photovoltaic development in Northwest China, where favorable conditions offer considerable potential for large-scale photovoltaic generation. These regions possess rich solar resources and extensive land suitability, making them optimal for photovoltaic power station construction. In contrast, southeastern coastal areas and southern provinces are less suitable for photovoltaic development due to constraints in land availability and solar radiation levels. This study provides valuable insights for strategic photovoltaic development planning in China.